Effect of Cynara cardunculus L. var. altilis (DC) in inflammatory bowel disease - Mateus, Vanessa (2022)
Cynara cardunculus L. var. altilis (DC) is a plant generally associated as an ingredient in the Mediterranean diet. The polyphenols present in this plant provide pharmacological and nutritional properties. C. cardunculus L. has been used throughout animal studies, which demonstrated an anti-inflammatory effect. Inflammatory bowel disease (IBD) is a chronic inflammatory disorder of the gastrointestinal tract. Since there is not a known cure, the research of new possible pharmacological approaches is essential. This study aims to evaluate the effect of an aqueous extract of C. cardunculus L. dry leaves in a 2,4,6-Trinitrobenzenesulfonic acid (TNBS)-induced colitis model. Methods: CD-1 mice with TNBS-induced colitis received an intraperitoneal (IP) administration of C. cardunculus L. once per day for 4 days. Results: The C. cardunculus L. demonstrated a beneficial effect in this experimental model of IBD with anti-inflammatory action through the reduction of tumor necrosis factor (TNF)-α levels. It also demonstrated a beneficial influence on the extra-intestinal manifestations related to IBD, with the absence of significant side effects of its use. Conclusions: The extract of C. cardunculus L. dry leaves can become an interesting tool for new possible pharmacological approaches in the management of IBD.